EJMM 2020
DOI: 10.51429/ejmm29421
|View full text |Cite
|
Sign up to set email alerts
|

Study the Role of Tp53 in the Development of Hepatocellular Carcinoma in HCV Infected Patients

Abstract: Background: Hepatocellular carcinoma (HCC) is considered as the primary malignancy of the liver that usually occurs on top of chronic viral hepatitis. The TP53 (tumor protein 53) is a tumor suppressor gene which is the key in tumor development and progression and the single nucleotide polymorphism (SNP) of the p53 gene codon 72 (p53Arg/Pro) changes the structure of the protein. Objectives: to determine the association of the TP53 Arg72Pro polymorphism with the risk of HCC development in Hepatitis C virus (HCV)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This suppression of p53 expression causes the transformation of infected hepatocytes into cancerous cells. It has also been demonstrated that not only mutations but also polymorphism of the p53 gene increases the risk of HCC in HCV-infected Egyptian patients . The aim of this study is to observe the TP53 gene expression and its association with different combinations therapies administered to the studied infected population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suppression of p53 expression causes the transformation of infected hepatocytes into cancerous cells. It has also been demonstrated that not only mutations but also polymorphism of the p53 gene increases the risk of HCC in HCV-infected Egyptian patients . The aim of this study is to observe the TP53 gene expression and its association with different combinations therapies administered to the studied infected population.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been demonstrated that not only mutations but also polymorphism of the p53 gene increases the risk of HCC in HCV-infected Egyptian patients. 21 The aim of this study is to observe the TP53 gene expression and its association with different combinations therapies administered to the studied infected population. If the administered drug is positively regulating the expression of TP53 gene might be a role to curb the chances of developing liver complications.…”
Section: Discussionmentioning
confidence: 99%